Maya salt works - McKillop, Heather Irene, 1953- (Maya studies., 2019)
This book includes evaluation of the economics of salt production and trade from analyses of the spatial patterning of wooden buildings and associated artifacts that were mapped on the sea floor at the Paynes Creek Salt Works. The book describes the discovery and mapping of the wooden architecture as well as the associated pottery and other artifacts on the surface and embedded in the sea floor during a systematic search for salt production in a large, salt-water lagoon system, Punta Ycacos Lagoon, in southern Belize.